Characterization of nano-hydroxyapatite-collagen and epigallocatechin-3-gallate (EGCG) composites by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy - Elline; Eko Fibryanto; Hiroko Gabriela Amanda (Wolters Kluwer Medknow Publications, 2022)
Background: Calcium hydroxide (Ca(OH)2) is most commonly used in vital pulp therapy, and it is the gold standard of pulp capping materials; however, it shows several limitations, including facile dissolution, stimulation of reparative dentin with tunnel defects, and inflammation. A previous study reported that nano-hydroxyapatite (nHA) might induce reparative dentin with no tunnel defects much better than Ca(OH)2. Another study reported that the addition of epigallocatechin-3-gallate (EGCG) to collagen (Col) gel can increase pulp cell proliferation and differentiation via the change in its mechanical properties. Objective: In this study, nHA-Col and EGCG composites were characterized by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Methods: Each material (i.e., nHA, Col type 1, and EGCG) was dissolved in 2 mL of deionized water. Three groups with varied nHA:Col ratios were prepared: 40:60 (group 1), 50:50 (group 2), and 60:40 (group 3). Each solution was mixed together using a magnetic stirrer at 40°C, followed by the addition of 2% hydroxypropyl methylcellulose (HPMC) into the mixture. Morphology observation, Ca/P ratio, crystallographic phase analysis, and functional group analysis were investigated by SEM-EDS, XRD, and FTIR. Results: SEM-EDS analysis revealed irregular agglomerated nHA between Col fibrils and a non-stoichiometric Ca/P ratio (>1.67). XRD analysis revealed hexagonal-phase nHA. FTIR analysis revealed chemical interaction between nHA, Col, and EGCG. Conclusions: SEM-EDS and XRD analysis confirmed that nHA does not change when it is mixed with Col and EGCG, and FTIR analysis revealed hydrogen bonding among materials.